2014
DOI: 10.1371/journal.pone.0106993
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic Acid Ameliorates Fructose-Induced Metabolic Syndrome in Rats

Abstract: The metabolic syndrome (MS) is characterized by insulin resistance, dyslipidemia and hypertension. It is associated with increased risk of cardiovascular diseases and type-2 diabetes. Consumption of fructose is linked to increased prevalence of MS. Ursodeoxycholic acid (UDCA) is a steroid bile acid with antioxidant, anti-inflammatory activities and has been shown to improve insulin resistance. The current study aims to investigate the effect of UDCA (150 mg/kg) on MS induced in rats by fructose administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 68 publications
(79 reference statements)
6
52
0
Order By: Relevance
“…101,102 Rodent models even suggest UDCA may be therapeutic in fructose-induced metabolic syndrome. 103 Recently, trials have been underway to determine the efficacy of UDCA to prevent colorectal adenoma recurrence, and results have been mixed. [104][105][106] Animal models have suggested that UDCA can prevent azomethane-induced colon carcinogenesis.…”
Section: Inactivation Of Ursodeoxycholic Acid By 7b-dehydroxylationmentioning
confidence: 99%
“…101,102 Rodent models even suggest UDCA may be therapeutic in fructose-induced metabolic syndrome. 103 Recently, trials have been underway to determine the efficacy of UDCA to prevent colorectal adenoma recurrence, and results have been mixed. [104][105][106] Animal models have suggested that UDCA can prevent azomethane-induced colon carcinogenesis.…”
Section: Inactivation Of Ursodeoxycholic Acid By 7b-dehydroxylationmentioning
confidence: 99%
“…AGE generation is an unavoidable and irreversible process (Fu et al, 2014). Research has demonstrated that the generation and accumulation of a large number of AGEs in vivo play a vital role in the development and acceleration of OA (Mahmoud and Elshazly, 2014); moreover, these act as the molecular foundation for the effect of age on OA. However, its mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Ursodeoxycholic acid (UDCA), a hydrophilic bile acid, is used in this experiment as a reference treatment for NAFLD, and is known to act by competitive displacement of hepatotoxic hydrophobic endogenous bile acids that facilitate apoptosis, minimizing their toxicity and leading to a decrease in oxidative stress and hepatic injury (Mahmoud & Elshazly, 2014).…”
Section: Introductionmentioning
confidence: 99%